Impact of Obesity on Appetite‐Related Behaviors and Biomarkers in Older Adults: A Cross‐Sectional Study - Sean J. Iwamoto; Tanya M. Halliday; Jason R. Tregellas; Kristina T. Legget; Allison K. Hild; Marc‐André Cornier (Obesity Science & Practice, 2025)
ABSTRACT Objective Although aging is associated with reduced hunger and energy intake (EI), obesity is increasing in older adults. This study aimed to identify appetite regulation differences between older adults with obesity and older adults with normal weight (NW). Methods This cross‐sectional study recruited older adults with obesity (BMI 30–40 kg/m2) and NW (BMI < 25 kg/m2) aged 65–85 years. Fasting appetite‐related behavioral questionnaires were collected. Ghrelin, polypeptide YY [PYY], glucagon‐like peptide‐1 [GLP‐1], glucose, insulin, and triglycerides were measured fasting and every 30 min for 3 h following a test breakfast, and the incremental area under the curve (iAUC) was calculated. Results 13 older adults with obesity (aged 70.8 ± 4.0 years, 54% female, BMI 33.1 ± 3.6 kg/m2) and 14 with NW (aged 70.8 ± 5.3 years, 71% female, BMI 22.5 ± 2.1 kg/m2) were analyzed. Compared to older adults with NW, older adults with obesity had higher disinhibition and perceived hunger (p < 0.001 and p < 0.05, respectively), lower confidence in preventing overeating (p < 0.05), higher fasting GLP‐1 and insulin (both p < 0.05), and higher PYY and insulin iAUCs (p < 0.01 and p < 0.05, respectively). Conclusion Despite similar meal‐related appetite and EI, older adults with obesity had higher fasting disinhibition, perceived hunger, GLP‐1 and insulin, higher PYY and insulin iAUCs, and lower confidence in preventing overeating than those with NW. These differences between older adults with obesity and NW have implications for tailored obesity treatments in older adults.